Multi-Omics Profiling Identifies Pathways Associated With CD8+ T-Cell Activation in Severe Aplastic Anemia - You, Xing; Yang, Qiong; Yan, Kai; Wang, Song-Rong; Huang, Rong-Rong; Wang, Shun-Qing; Gao, Cai-Yue; Li, Liang; Lian, Zhe-Xiong (Frontiers in Genetics, 2022)
Severe aplastic anemia (SAA) is an autoimmune disease characterized by immune-mediated destruction of hematopoietic stem and progenitor cells. Autoreactive CD8+ T cells have been reported as the effector cells, however, the mechanisms regulating their cell activation in SAA remain largely unknown. Here, we performed proteomic and metabolomic analysis of plasma and bone marrow supernatant, together with transcriptional analysis of CD8+ T cells from SAA patients and healthy donors to find key pathways that are involved in pathogenic CD8+ T cell activation. We identified 21 differential proteins and 50 differential metabolites in SAA patients which were mainly involved in energy metabolism, complement and coagulation cascades, and HIF-1α signaling pathways. Interestingly, we found these pathways also enriched in T cells from SAA patients by analyzing available single-cell RNA sequencing data. Moreover, CD8+ T cells from SAA patients contain a highly activated CD38+ subset, which was increased in the bone marrow of SAA patients and a murine model of SAA. This subset presented enriched genes associated with glycolysis or gluconeogenesis pathway, HIF-1α signaling pathway and complement associated pathways, all of which were of importance in T cell activation. In conclusion, our study reveals new pathways that may regulate CD8+ T cell activation in SAA patients and provides potential therapeutic targets for SAA treatment.